Analisis Rasio Likuiditas, Solvabilitas, dan Rentabilitas Untuk Menilai Kinerja Keuangan BMT Itqan Bandung Periode 2019 – 2023 - Hera Nurhalizah Rahim; Vino Vebrianto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to find out whether the liquidity ratio, solvency ratio, and profitability ratio can assess the financial performance of the BMT ItQan Sharia Cooperative for the 2019 – 2023 period. The results of the financial ratio analysis were then compared with the guidelines established by the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 07 / Per / Dep.6 / IV / 2016, Regulation of the Deputy for Supervision regarding the Guidelines for Assessing the Health of Savings and Loans Cooperatives and Sharia Financing, as well as Savings and Loans Units and Sharia Financing. Trend analysis was then used to determine whether the trend is increasing or decreasing. This research is descriptive qualitative, and was conducted by collecting and evaluating data before presenting the findings as numerical data. Quantitative data analysis, secondary data, interviews, and documentation procedures are all used in data analysis. Based on the research findings, the financial performance of the ItQan Sharia Cooperative BMT from 2019 to 2023 consists of: The financial performance of the ItQan Sharia Cooperative from 2019 to 2023 consists of: 1) The liquidity ratio measured by the Cash ratio received a value of 21% with a fairly liquid performance with an upward trend trend. 2) The solvency ratio measured by the debt to assets ratio received a score of 79.2% with poor performance with an upward trend, and the debt to equity ratio received a score of 508% with poor performance due to an upward trend. 3) The profitability ratio measured by return on assets gets a value of 1% with low performance with a downtrend trend, return on equity gets a value of 5% with low performance with a downtrend trend.